The poverty and wealth of regions (assumptions, hypotheses, examples) - Grzegorz Gorzelak (Employment and regional development policy: Market efficiency versus policy intervention, 2004)
There exist many possible approaches to analyse the poverty and wealth of regions (growth theory, economic base theory, polarised growth theories, dependence theories, centre vs. periphery approaches). All these line of research frequently tend to be one-side, and some times too particularised, which impairs their explicatory - and therefore applicatory - potential. However, it is possible to attempt a generalised outlook on regional development process in a longer, comparative historical perspective. The present work is an endeavour to expound such a theoretical proposition in a generalised and dynamic formulation of the substance and mutual relations between key factors of regional development (regional features, the development paradigm - location criteria - and external stimuli). This theoretical model aims to provide a comprehensive dynamic view of the factors and circumstances determining the development of regions. One of the lessons derived from the theoretical proposition is that maintaining high competitiveness requires continuous adjustments of the regional features to the prevailing - and changing - location criteria. The way the external stimuli are utilised represents also a fundamental factor behind regional development.
hdl:10419/62287; http://EconPapers.repec.org/RePEc:zbw:arlssd:5
Keywords: 330